E-FIRUZ approach on e-learning platform for effective immersive learning - Firuz-Akhtar Lubis; Nur Asyiqin Zohkarnain (Penerbit Universiti Kebangsaan Malaysia, 2024)
Education in the period of Industrial Revolution 4.0 (IR4.0) is a new wave in the world of education today. Various online learning systems have been developed in line with the latest technological advancements to provide immersive learning experiences. Educators today need to design engaging online learning styles, particularly for the use of online learning platforms such as UKMFolio. This study discusses the FIRUZ approach as one effective method to facilitate the creation of learning experiences on online learning platforms like UKMFolio. The study employs a quantitative approach in the form of a survey. Assessment is conducted using a questionnaire administered to students enrolled in the Comparative Literature course on UKMFolio. In this particular study, convenience sampling has been utilized, and descriptive analysis is conducted using SPSS software. Overall, students in the Comparative Literature course provided positive feedback regarding the utilization of the FIRUZ approach as an e-learning method on UKMFolio. Consequently, the FIRUZ approach in e-learning holds significant benefits as it possesses commercial value that can be utilized by academic professionals across various fields.